Petrogenesis of late triassic high-silica granites in the North Qiangtang terrane, central Tibetan Plateau - Ji, Changjun; Liu, Bin; Chen, Yun; Wu, Zhenhan; Chen, Chong (Frontiers in Earth Science, 2024)
Although high-silica granites can provide unique insights into the maturity of the continental crust and the rare metal enrichment, the origin of high-silica granitic magmatism is still equivocal. In this paper, we present an integrated study of the zircon U-Pb geochronology and trace elements, whole-rock geochemistry, Sr-Nd isotopes for the two typical high-silica granites (include the Longbao granitic porphyry and the Yushu granite) in the North Qiangtang terrane, central Tibetan Plateau. The zircon geochronological data indicate that those highsilica granites crystallized at 217~214 Ma. All the samples from the Longbao granitic porphyry and the Yushu granite exhibit high SiO2 low MgO, depletion of Ba, Nb, Sr, P, and Ti, and enrichment of Th and U. They show relatively high ( 87 Sr/ 86 Sr)i ratios of 0.7120 ~ 0.7136 and low εNd(t) values of -8.58 ~ -7.58, together with their old two-stage Nd model ages (1.6 to 1.7 Ga), indicating the involvement of crustal materials. The geochemical and isotopic variations indicate that the studied high-silica granites were mainly produced by the dehydration melting of a muscovite (Ms)-bearing source, and the Triassic turbidites might be a good candidate for the magma source. Combined with the new regional studies, it can be concluded that partial melting of Triassic turbidites induced by the slab roll-back might be the key factor controlling the origin of Late Triassic magmatism in the North Qiangtang terrane.